KEDISIPLINAN GURU DALAM MENGAJAR MEMBAWA DAMPAK POSITIF BAGI TUMBUH KEMBANG PESERTA DIDIK - Susanto, Deni (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
This study aims to comprehensively describe the impact of teacher discipline in teaching on student growth and development, encompassing cognitive, affective, and psychomotor aspects. Employing a descriptive qualitative approach with data collection techniques including observation and interviews at SMP Negeri 3 Kampak, Trenggalek Regency, this research involved teachers and students as subjects. The findings revealed a significant increase in the level of student growth and development following the implementation of a teacher discipline enhancement program. The level of student growth and development rose from 77.68% to 84.58%, as reflected in improvements across cognitive indicators (average scores, critical thinking skills, problem-solving abilities), affective indicators (responsibility, learning motivation, self-discipline), and psychomotor indicators (practical/work skills, punctuality in task completion). These findings indicate that teacher discipline creates a conducive learning environment, provides a positive role model, and effectively facilitates the holistic development of students. This research underscores the importance of teacher discipline as a crucial element in improving the quality of education and student growth and development. ABSTRAKPenelitian ini bertujuan untuk menggambarkan dampak kedisiplinan guru dalam mengajar terhadap tumbuh kembang peserta didik secara komprehensif, meliputi aspek kognitif, afektif, dan psikomotorik. Menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi dan wawancara di SMP Negeri 3 Kampak Kabupaten Trenggalek, penelitian ini melibatkan guru dan peserta didik sebagai subjek. Hasil penelitian menunjukkan adanya peningkatan signifikan pada tingkat tumbuh kembang peserta didik setelah implementasi program peningkatan kedisiplinan guru. Tingkat tumbuh kembang peserta didik meningkat dari 77,68% menjadi 84,58%, yang tercermin dalam peningkatan pada indikator kognitif (rata-rata nilai, kemampuan berpikir kritis, pemecahan masalah), afektif (tanggung jawab, motivasi belajar, kedisiplinan diri), dan psikomotorik (keterampilan praktik/kerja, ketepatan waktu penyelesaian tugas). Temuan ini mengindikasikan bahwa kedisiplinan guru menciptakan lingkungan belajar yang kondusif, menjadi teladan positif, dan secara efektif memfasilitasi perkembangan holistik peserta didik. Penelitian ini menegaskan pentingnya kedisiplinan guru sebagai elemen krusial dalam meningkatkan kualitas pendidikan dan tumbuh kembang peserta didik.